Non-communicable disease risk factors among Orang Asli in Tasik Chini, Pahang. - Kamaruzaman, Nor Azam; Pasi, Hafizah (2019)
Introduction: The health status of Orang Asli (OA) in Malaysia often lag behind other races with under-nutrition and communicable diseases remain significant. While there is an upward trend of non-communicable diseases (NCD) in this country due to modernisation of lifestyle, how this change affecting OA is a public health interest. Materials and method: A community based survey was conducted involving 225 OA from Jakun tribe aged above 18 years living in three villages around Tasik Chini, Pahang in 2017. Results: There were low prevalence of overweight and high blood pressure (18.8% and 14.2%). Random blood sugar 5.6 mmol/L was found in 23.4% but only five villagers (0.02%) were eventually diagnosed with diabetes mellitus. Majority (63.7%) of OA in the three villages smoke products of tobacco. Conclusion: The NCD risk among this fringe OA community is still insignificant as shown by low prevalence of overweight, high blood pressure, and diabetes even when compared to national figures for other Bumiputera in Malaysia (30%, 18.6%, and 10.7% respectively). However, the prevalence of smoking was strikingly higher than 2015 national figure for other Bumiputera (25.8%). This is contributed by high rate of smoking among women and established cultural practice. The findings highlighted the need for customization in smoking intervention for OA.